Volumetric nasal cavity analysis in children with unilateral and bilateral cleft lip and palate. (12th August 2015) - Farzal, Zainab; Walsh, Jonathan; Lopes de Rezende Barbosa, Gabriella; Zdanski, Carlton J.; Davis, Stephanie D.; Superfine, Richard; Pimenta, Luiz A.; Kimbell, Julia S.; Drake, Amelia Fischer
Abstract : Objectives/Hypothesis: Children with cleft lip and palate (CLP) often suffer from nasal obstruction that may be related to effects on nasal volume. The objective of this study was to compare side:side volume ratios and nasal volume in patients with unilateral (UCLP) and bilateral (BCLP) clefts with age‐matched controls. Study Design: Retrospective case–control study using three‐dimensional (3D) nasal airway reconstructions. Methods: We analyzed 20 subjects (age range = 7–12 years) with UCLP and BCLP from a regional craniofacial center who underwent cone beam computed tomography (CT) prior to alveolar grafting. Ten multislice CT images from age‐matched controls were also analyzed. Mimics software (Materialise, Plymouth, MI) was used to create 3D reconstructions of the main nasal cavity and compute total and side‐specific nasal volumes. Subjects imaged during active nasal cycling phases were excluded. Results: There was no statistically significant difference in affected:unaffected side volume ratios in UCLP ( P = .48) or left:right ratios in BCLP ( P = .25) when compared to left:right ratios in controls. Mean overall nasal volumes were 9, 932 ± 1, 807, 7, 097 ± 2, 596, and 6, 715 ± 2, 115 mm 3 for control, UCLP, and BCLP patients, respectively, with statistically significant volume decreases for both UCLP and BCLP subjects from controls ( P < .05). Conclusions: This is the first study to analyze total nasal volumes in BCLP patients. Overall nasal volume is compromised in UCLP and BCLP by approximately 30%. Additionally, our finding of no major difference in side:side ratios in UCLP and BCLP compared to controls conflicts with pre‐existing literature, likely due to exclusion of actively cycling scans and our measurement of the functional nasal cavity. Level of Evidence: 3b. Laryngoscope, 126:1475–1480, 2016